Effect of Competency-Based Training and Career Planning on Employee Performance at PT PLN (Persero) UP3 Palopo, Indonesia - Mutia Nurfadila Aris; Indra Kusdarianto; Altri Wahida (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to analyze the effect of competency-based training and career planning on employee performance at PT PLN (Persero) UP3 Palopo. Methodology: The research method used is a quantitative approach with data collection techniques through questionnaires to 52 respondents selected from 119 employees. Data analysis uses validity and reliability tests, multiple linear regression, t-tests, and f-tests. Results: The results of this study indicate that competency-based training and career planning have a positive and significant effect on employee performance both partially and simultaneously. Findings: The findings confirm that both competency-based training and career planning serve as critical drivers in enhancing employee performance within the state-owned electricity sector. Novelty & Originality: The novelty of this study lies in the simultaneous examination of competency-based training and career planning within the specific context of a regional service unit of a state-owned electricity company in Palopo, an organizational setting that has received limited empirical attention in prior research. Its originality emerges from the integrated analysis of these two human resource development variables as complementary rather than independent factors, offering a holistic perspective on performance improvement strategies in the Indonesian state-owned enterprise sector. Conclusions: The implications of this study show the importance of companies in improving the quality of training and providing clear career planning to improve employee performance. The study concludes that investing in structured training programs and transparent career development pathways is essential for optimizing workforce productivity and achieving organizational goals. Type of Paper: This paper is an empirical research paper.